High-Throughput Metabolomics Evaluate the Efficacy of Total Lignans From Acanthophanax Senticosus Stem Against Ovariectomized Osteoporosis Rat - Zhang, Ai-hua; Ma, Zhi-ming; Sun, Hui; Zhang, Ying; Liu, Jian-hua; Wu, Fang-fang; Wang, Xi-jun (Frontiers in Pharmacology, 2019)
Postmenopausal osteoporosis (PMOP) is a common clinical illness in postmenopausal women, but there is no effective drug at present. Metabolomics approach was used to explore the potential biomarkers of PMOP and evaluate the efficacy and therapeutic targets of total lignans in the stem of Acanthophanax senticosus (ASSL) on the ovariectomized osteoporosis model rats. UPLC/MS and pattern recognition methods were used for serum metabolites discovery to illustrate the pathological mechanism of PMOP model rats, and then revealing the intervention effect of ASSL. The pattern recognition result showed that serum metabolic profiles of the sham operation group and the model group were clustered clearly, and 16 potential biomarkers were finally identified (7 in positive ion mode and 9 in negative ion mode), and they are involved in 15 related metabolic pathways. After oral administration of ASSL, 10 biomarkers were found to be significantly up-regulated and mainly regulated metabolic pathways include unsaturated fatty acid biosynthesis, linoleic acid metabolism, and arachidonic acid metabolism, primary bile acid synthesis, tyrosine metabolism, etc. Our study demonstrated that the ASSL could affect the endogenous metabolites related metabolic mechanism, provides a pharmacological basis of the ASSL for PMOP treatment.